2009
DOI: 10.1097/aog.0b013e31819b413f
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Patterns of Recurrence for International Federation of Gynecology and Obstetrics (FIGO) Stages I and II Squamous Cell Vulvar Cancer

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 28 publications
3
45
2
4
Order By: Relevance
“…This is coupled with assignment of all lower tract non-metastatic tumors to stage II, also without discrimination by size. Unlike other studies [11], and unpublished data [9] we observed that size may be an important independent prognostic factor when lymph nodes are negative. This was corroborated by Homesely et al [12] who delineated that diameter is an important independent risk factor irrespective of nodal status.…”
Section: Discussioncontrasting
confidence: 70%
“…This is coupled with assignment of all lower tract non-metastatic tumors to stage II, also without discrimination by size. Unlike other studies [11], and unpublished data [9] we observed that size may be an important independent prognostic factor when lymph nodes are negative. This was corroborated by Homesely et al [12] who delineated that diameter is an important independent risk factor irrespective of nodal status.…”
Section: Discussioncontrasting
confidence: 70%
“…A significant decrease of postoperative morbidity was achieved by the application of separate inguinal incision in the shape of the letter "S", sharp surgical preparation to form the sharp edges of the wound with a part of the subcutaneous tissue that provides adequate nutrition of the skin, application of vacuum drains and suturing skin with synthetic seaming materials under minimally expressed tension. According to the cumulative results from the literature the total percentage of recurrence after surgical treatment of vulvar cancer ranges from 15 to40% and is related to the size, depth of invasion of malignant lesions and positive regional lymph nodes [16][17][18]. In our study, recurrences were recorded in 7 (17%) patients, which is slightly higher than in the previous period when five (12.8%) cases were recorded.…”
Section: Discussioncontrasting
confidence: 61%
“…23 The stable mortality rates that we observed in women younger than 60 years may reflect the fact that younger women are more likely to present with earlystage disease, which has a more favorable prognosis, and most recurrences are localized to the vulva and have a high cure rate, usually with further excision. 25 In conclusion, we found that the incidence of vulvar cancer has substantially increased in Australian women younger than 60 years. Although an ecologic analysis of the type presented here cannot demonstrate causality, this increase is consistent with findings from other developed countries and also with the likely timing of increasing levels of population exposure to HPV due to changing sexual mores in women born from the 1950s onward.…”
Section: Discussionmentioning
confidence: 58%